The adsorption of Reactive Orange 16 and Basic Blue 3 from aqueous solution using quaternized blue swimmer crab carapace - Chuah, You Jian; Tan, Yen Ping; Abdullah, Abdul Halim (Universiti Putra Malaysia Press, 2018)
The crab carapace is a waste which cannot be decomposed. This waste was used to remove the Reactive Orange 16 (RO16) and Basic Blue 3 (BB3) from aqueous solution at different operational parameters such as pH, mass load, the concentrations of dye and the temperature. The crab collected was modified to obtain quaternized crab (QC) using (3-chloro-2-hydroxypropyl) trimethylammonium chloride solution (C6H15Cl2NO, 65% w/w in water). The pH of the dyes solution was varied from pH 4 to 10. The highest adsorption percentage was achieved at pH 7 for both dyes. Increasing the QC mass for the adsorption process had granted an increase of dyes removal percentage. The highest adsorption percentage was achieved at 91.00% for RO16 and 29.40% for BB3 dyes with 7.5 g/L QC used. However, the adsorption capacity of QC decreased with higher QC mass because the dye molecules occupied on the surface and prevented other molecules to diffuse into the QC. At higher concentration beyond 20 mg/L and 10 mg/L of RO16 and BB3, respectively, the maximum adsorption was achieved at 2.5362 mg/g and 0.6812 mg/g. The adsorption of both dyes by QC was best fitted using Langmuir isotherm model, explaining the adsorption mainly occurred as a single layer on the surface of QC. Comparison to the results obtained from the kinetic models, the adsorption was chemisorption in nature. According to the thermodynamic studies, the adsorption of RO16 was an exothermic, while BB3 was an endorthermic process.